Effect of supplementation on intake of minerals, milk yield and blood biochemical profile in lactating camels under traditional and semi intensive system - SAINI, N; SINGH, N; KIRADOO, B D (The Indian Journal of Animal Sciences, 2010)
Assessment of mineral status from feeding trial revealed that straw feeding under traditional system resulted in deficiency of Ca, P, Cu, Zn and Mn. Effect of supplementation of these minerals was evaluated in terms of intake of dry matter, milk yield and body weight as well as on blood biochemical profile in 8 Bikaneri camels. Group 1 camels were managed under traditional system with supplementary feeding of straw at evening. Camels of group 2 were fed same straw with concentrate and mineral mixture under intensive system. Strategic supplementation resulted in significant increase in dry matter (g/kg 0.75) intake and consequently higher mineral intake in respective group compared to control. The group 2 camels produced more milk (6.11 litre/day) than group 1 (5.37 litre/day) with an average of 463.63 and 408.34 litres, respectively. The dam of group 1 lost 15 kg body weight while dam of group 2 gained 16.75 kg weight with daily gain of 500 g/day with supplementation and thus indicated positive effect on body weight of dam. Similarly, the calves of supplemented group 2 had significantly faster growth with daily gain of 739.25 g/day than non-supplemented group 1 (631.72 g/day). Average blood minerals concentration was above the critical limit and values of P, Cu, Zn and Mn showed significant increase with supplementation of these minerals. Concentration of total protein was significantly higher in supplemented group (6.69 mg%) compared to control (5.95 mg%). The results indicated that in the existing traditional feeding system supplementation of Ca, P, Cu and Zn are required in diet of lactating camels and dietary supply of these nutrients improved production performance of camel.